Removal of chromium (VI) from aqueous solution by natural clay - Algamal, Yousif Mohamed (Archives of Business Research, 2018)
The adsorption of chromium (VI) from aqueous solution was carried out using natural clay from western area in Saudi Arabia. The adsorbents used are characterized by X-ray diffraction (XRD) and other physico-chemical techniques. The various parameters affecting the adsorption process were investigated involving effect of initial concentration of Cr (VI) ion, temperature factor, dosage of adsorbent, pH of the solution, contact time and rotational per minute (RPM). Optimum conditions for adsorption process were; 50 mg/L-1 initial concentration of Cr(VI), adsorbent dose =1g, temperature 25oC, 3 hours contact time and pH=2, the obtained results were used to calculate the adsorption efficiency. Removal of chromium ion was found as highly depends on pH and initial Cr (VI) concentration of the solution. Langmuir isotherm was applied to get a maximum adsorption capacity of 18.68 mg/g. Although experimental data confirm with Langmuir isotherm model. The results of this study confirm that the material can be considered as effective adsorbents for the removal of chromium (VI).